1991
DOI: 10.1037/0735-7044.105.3.459
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial asymmetries and interocular transfer in the split-brain rat.

Abstract: Interocular transfer (IOT), hemispheric superiority, and cerebral dominance were examined in split-brain female albino rats. Callosum-sectioned and intact animals were monocularly trained in the Morris water maze and tested in IOT and reversal phases. In the IOT phase, split-brain rats entered more nontarget quadrants and headed less accurately toward the platform than did controls. For both split-brain animals and controls, right-eye training resulted in shorter latencies and fewer nontarget entries than did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Examination of all mounted sections from the brains of surgical subjects indicated that the extent of callosal transsection was approximately 89% to 100%. This lies well within the range considered to constitute a total transsection in the literature on rats (1,5).…”
Section: Discussionsupporting
confidence: 61%
“…Examination of all mounted sections from the brains of surgical subjects indicated that the extent of callosal transsection was approximately 89% to 100%. This lies well within the range considered to constitute a total transsection in the literature on rats (1,5).…”
Section: Discussionsupporting
confidence: 61%
“…(Lateralization has been demonstrated for other regions of the rat brain involved in solving spatial tasks, e.g. Adelstein & Crowne, 1991; King & Corwin, 1992) By contrast, hippocampal lateralization in humans is well known (Smith & Milner, 1989), but it is not necessarily different aspects of spatial cognition that lateralize. In humans, the right hippocampus has been reported to be more heavily recruited in tasks of navigation, the left more heavily recruited in the encoding of episodic memories (Burgess et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be that the "untrained" eye does not have access to the representation of the visual information that was clearly acquired and stored during training. Given these findings, it appears that additional, invasive surgeries to further disconnect the cerebral hemispheres (e.g., cutting the optic chiasm or corpus callosum; e.g., Adelstein & Crowne, 1991;Chang & Greenough, 1982;Crowne et al, 1994;Shinohara et al, 2012) are not required to achieve a highly lateralized training effect, at least for the behavioral paradigm used in the present investigation.…”
Section: Discussionmentioning
confidence: 87%
“…An advantage of the mask designed here is the ease of switching the eye patch between the two eyes, thus allowing for an uncomplicated study of interocular transfer of visual information. The noninvasive and relatively stress-free nature of the eye patch devised here clearly offers advantages over alternative methods of restricting visual input, such as adhesive eye patches (Adelstein & Crowne, 1991;Crowne et al, 1994), lid suturing (Chang & Greenough, 1982;Fig. 2 Monocular visual discrimination performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation